JAM DIGITAL DENGAN OUTPUT SUARA UNTUK PENYANDANG TUNANETRA - Fikri Mardianto; Dandi Efendi; Ocsirendi; Indra Dwisaputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Time is one of the most important elements in human life. Everyone definitely needs time information, so a tool was created to know the time, namely a clock. However, not everyone has the opportunity to be able to use the clock like how it usually is. For example, people with visual impairments in special schools. Therefore, in this final project we made a digital clock that aims to help blind people to know the time at a certain time and can be used conventionally in special schools, where this tool can work in two ways, namely calling time data on the RTC to displayed on the led matrix and compares the time data in a 24-hour format on the RTC with 4 logic programs contained in each push button, where each push button will emit a sound according to its logic on the speaker or headset.  So that the sound issue can be heard clearly, the duration is used for each logic with the following results: The sound of time in the form of a number with 2 syllables requires a duration of 1000 ms, while the normal mode voice with 4 syllables also requires a duration of 1000 ms. Based on the results of these data, it can be concluded that the longer the pronunciation of the word, the greater the duration required, even though it has different syllables.